2005
DOI: 10.1016/j.jcrs.2004.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid combined with mannitol to improve protection against free-radical endothelial damage: Experimental Model

Abstract: All of the OVDs tested efficiently reduced endothelial lesions against free radicals compared with the control group in which no OVD was used. The following sequence for the efficacy of endothelial cell protection was established: Visiol>Viscoat>Healon>no OVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 13 publications
(17 reference statements)
0
22
0
Order By: Relevance
“…SH is the main component of the ground substance of the connective eye tissues; it is already widely used alone in most of the commercial OVDs because of its capability of protecting against free-radical endothelial damage [22], and to its welldocumented mucoadhesive properties [23][24][25][26]. Chitosan thanks to its mucoadhesive properties has been proposed for topical use in ophthalmology and in mucosal sitespecific systems [11][12][13].…”
Section: Article In Pressmentioning
confidence: 99%
“…SH is the main component of the ground substance of the connective eye tissues; it is already widely used alone in most of the commercial OVDs because of its capability of protecting against free-radical endothelial damage [22], and to its welldocumented mucoadhesive properties [23][24][25][26]. Chitosan thanks to its mucoadhesive properties has been proposed for topical use in ophthalmology and in mucosal sitespecific systems [11][12][13].…”
Section: Article In Pressmentioning
confidence: 99%
“…Addition of an antioxidant to HA has already been studied also in ophthalmology. In an animal model of oxidative stress using hydrogen peroxide (H 2 O 2 ), Belda et al [25] showed that HA associated with a low concentration of mannitol (0.5%) better protected the corneal endothelium, than HA alone.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of other free radical scavengers in the OVDs (mannitol in Visiol and chondroitine sulphate in Viscoat) does not prevent MDA formation in this in vitro experiment. In a different study [26] , the authors demonstrated in vivo that OVDs containing sodium hyaluronate efficiently protected the endothelial cells against oxidative damage (H 2 O 2 ) in an experimental model with rabbits. The OVDs with higher concentrations of sodium hyaluronate (Visiol and Viscoat) achieved better endothelial protection.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium-hyaluronate-based products have already been shown to have a free radical (like hydroxyl radicals or peroxynitrite radicals) scavenging effect [26][27][28] . However, the scavenging reaction on sodium hyaluronate is followed by a breakdown of the molecule.…”
Section: Discussionmentioning
confidence: 99%